1.Rezolvati dupa modelul dat:
Model : ![(x+y)^{2} + 6(x+y)(x-y) + 9(x+y)^{2} = [(x+y) + 3(x-y)] (x+y)^{2} + 6(x+y)(x-y) + 9(x+y)^{2} = [(x+y) + 3(x-y)]](https://tex.z-dn.net/?f=%28x%2By%29%5E%7B2%7D+%2B+6%28x%2By%29%28x-y%29+%2B+9%28x%2By%29%5E%7B2%7D+%3D+%5B%28x%2By%29+%2B+3%28x-y%29%5D)
a)
Răspunsuri la întrebare
Răspuns de
1
a²+2x²-4a²+8x+4a²²-8x²=a²+2x²=(a+x)(a+2x)
ZuZuOFFICIAL:
Multumesc !
Alte întrebări interesante
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Ed. tehnologică,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă